The syndrome of multiple bodies: the transformative impact of the onlife existence on preadolescents - Digennaro, Simone (Frontiers in Education, 2024)
This conceptual paper explores the integration of technology and virtual spaces into preadolescents' lives, blurring the boundaries between the digital and physical worlds. It emphasises the profound implications of this integration on various aspects, including perception, reality, and interactions. The younger generations, deeply immersed in this reality, experience a transformation in their perception of the world, well-being, identity, and selfhood due to technology's pervasive influence. The fusion of online and offline experiences gives rise to a new form of existence, shaping a hybrid identity that can be manipulated and reconstructed in the virtual realm. However, this fluidity and transience of virtual life also pose risks and challenges to personal identity and societal ruptures. Educators face the dual challenge of effectively integrating technology into education while understanding its impact on the new generations. Social media usage influences the interlink between body and identity processes, challenging traditional notions of embodiment and raising questions about the malleability and multiplicity of identities in technologically mediated spaces. The proposed reflections seek to provide valuable guidance for educators in navigating this complex digital reality.